On the use of ambient odours to influence the multisensory experience of dining - Spence, C (Elsevier, 2021)
In recent years, a number of modernist chefs have started to pay more attention to the potential role of food or drink-extrinsic scents in enhancing their guest’s multisensory gastronomic experiences. This narrative review highlights the wide range of uses for such ambient, and/or food-extrinsic, aromas. Oftentimes, in a gastronomic setting, ambient scents have been introduced by chefs in order to help set the context for a particular dish, and/or to assist with the storytelling that surrounds a specific element within an experiential meal. Ambient scents have also been introduced in order to induce a specific mood and/or to trigger nostalgia in the minds of diners. Food-extrinsic scents have, on occasion, even been used deliberately to modify the taste/flavour of the food or drink itself. At the same time, however, a number of sensory marketers have become increasingly interested in the idea of signature scents associated with branded food establishments and the role that they may play in inducing a desire to consume, and thus bias (or nudge) people’s food purchasing behaviour. A third use of food scents is to help people control their food consumption. This narrative review highlights both the opportunities and challenges that are associated with the use of ambient and/or dish-extrinsic scent in a gastronomic setting. Ultimately, the literature reviewed here highlights the somewhat different uses to which ambient (or product-extrinsic) food smells have been put in the gastronomic, artistic/theatrical, health-related, and mainstream restaurant contexts.